Initial Training of Primary School Teachers: Development of Competencies for Inclusion and Attention to Diversity - Carmen Nuria Arvelo-Rosales; Olga María Alegre de la Rosa; Remedios Guzmán-Rosquete (MDPI AG, 2021)
Teachers need to be prepared to attend to all learners regardless of their abilities or needs. This implies that future teachers must develop, throughout their initial training, the necessary competencies to provide inclusive education to all students. The aim of this research was to analyze the level of development of competencies related to inclusion and attention to diversity among university students of a degree in primary education. Based on the project developed by the European Agency for Development in Special Needs Education (EADSNE) on the profile of the inclusive teacher, an ad hoc survey was prepared based on the four fundamental competencies proposed: valuing student diversity, supporting all students, working as part of a team, and developing one's professional and personal qualities. This survey was administered to 440 students of the degree in primary education from the University of La Laguna (San Cristóbal de La Laguna, Spain). The results showed a positive development of the four competencies, with a higher development of the competencies of continuing professional development. It was also found that the students had the knowledge, skills, and attitudes necessary for promoting inclusion and encouraging attention to diversity in their classrooms.